JURIDICAL REVIEW OF SHIFTED OFFENSE IN COPYRIGHT LAW NUMBER 28 /2014 - Yati Nurhayati; Ifrani Ifrani (UNISSULA, 2019)
The objective of this study are: First, to find the reasoning behind changes in offenses in the Copyright Law number 28 /2014. Second, reviewing the impact of offense changes and their influence on the enforcement of copyright in Indonesia. This study uses a normative juridical method. Normative legal research is carried out through qualitative descriptive. While the legal material is collected, sorted and subsequently studied and analyzed for content, to obtain the level of synchronization, the feasibility of norms, and the submission of new normative ideas.The results of this study are that the complaint offense in the 2014 Copyright Law is suitable considering that copyright is something unformed. When a complaint is imposed, the copyright owner must know the details of the object of his creation. The impact of the offense change has become a crucial factor in the enforcement of copyright law in Indonesia. Given that so far the application of normal offenses seems to be running in place because law enforcers become passive and with complaints offense, all stakeholders can protect the copyright of the creator.